Exercise and Physical Activity Diversity - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
In this reflective opinion piece, we introduce the concepts of exercise diversity and physical activity diversity. Similar to dietary diversity and dietary variety, exercise/physical activity diversity represents part of a comprehensive target of ideal health, an objective parameter to audit one’s progress towards such a goal, and a means of accomplishing this aim. We define this concept as the number of types of exercise, the number of limbs and body parts exercised or muscle groups involved, the variety of intensity, or the number of variations in methods of exercise used. A non-weighted score may be allocated to each exercise, limb, and muscle group to get a raw idea of diversity. Keywords: Activity, exercise, fitness, obesity, overweight, physical fitness.